Impact of Intraoperative Radiotherapy on Cosmetic Outcome and Complications after Oncoplastic Breast Surgery. Issue 3 (May 2015) - Cracco, Silvia; Semprini, Gloria; Cattin, Federico; Gregoraci, Giorgia; Zeppieri, Mark; Isola, Miriam; Ceschia, Tino; Cedolini, Carla; Parodi, Pier Camillo
Abstract: Breast cancer is one of the most common tumors in the population worldwide. Conservative breast surgery (CBS) is one of the preferred surgical options, because both the oncologic and esthetic needs of the patient can be addressed. CBS surgical outcomes tend to be more effective with reduced chances of disease recurrence when radiotherapy (RT) treatment is considered as an adjunct treatment, either applied during surgery (IORT) and/or after (EBRT). The purpose of our study was to compare surgical outcomes between IORT and EBRT after CBS. In the past 5 years, we performed CBS in 489 patients in our clinic. Of these patients, 83 underwent adjunct treatment with IORT and 109 were treated with EBRT in accordance with our university approved clinical protocol. Surgical outcomes, early complication rates, and esthetic results were compared between these two groups of CBS patients, with a mean follow‐up time of 17 months. IORT allowed breast irradiation treatment to be performed without effecting overlying skin, thus cosmetic outcomes tended to be favorable. Esthetic postoperative results assessed with the Breast Cancer Conservation Treatment (BCCTcore) software showed that the differences between IORT and EBRT were not statistically significant (including those patients that underwent further oncoplastic techniques after EBRT). The disease recurrence rates between the two groups were not significantly different. IORT is a safe, fast, and feasible technique that provides effective and comparable CBS outcomes for patients with breast cancer.